2017
DOI: 10.1159/000458722
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations Due to Cirrhosis: Clinical Aspects in a Large Cohort of Italian Patients and Cost Analysis Report

Abstract: Background and Aim: Liver cirrhosis is characterized by high morbidity and mortality rates. This study was addressed to evaluate the epidemiological and economic impact of cirrhosis on hospitalizations in a large population in Italy. Methods: Epidemiological analysis was performed using hospital discharge sheets of 57,720 hospitalizations due to liver disease from 2006 to 2008, selected from the Veneto regional archive. In a sample of 100 randomly selected hospitalizations, a detailed cost analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…Long‐term treatment with albumin at the doses of 20 g twice per week significantly improved survival and therefore may be considered as a novel strategy, especially for patients in waiting list for LT, who could benefit most from a lengthening of life expectancy. In the group of patients treated with SOC, ascitic decompensation and HE were the main causes of hospitalization, similarly to the general population of patients with cirrhosis . Even if albumin administration did not reduce significantly the frequency and volume of paracentesis performed at DH, it prevented admissions as inpatient.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Long‐term treatment with albumin at the doses of 20 g twice per week significantly improved survival and therefore may be considered as a novel strategy, especially for patients in waiting list for LT, who could benefit most from a lengthening of life expectancy. In the group of patients treated with SOC, ascitic decompensation and HE were the main causes of hospitalization, similarly to the general population of patients with cirrhosis . Even if albumin administration did not reduce significantly the frequency and volume of paracentesis performed at DH, it prevented admissions as inpatient.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, plasma volume expansion secondary to renal water and sodium retention fuels ascites formation . Ascites is the complication which is most frequently responsible for hospital admission in patients with cirrhosis . Moreover, the development of ascites is a relevant unfavourable prognostic factor in cirrhosis since, after its occurrence, the mortality rate rises up to 50% within 2‐5 years …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with existing evidence demonstrating the safety and efficacy of DAA treatment with decompensated HCV cirrhosis patients, the findings of this study suggest that DAAs can attenuate some advanced forms of hepatic decompensation by resolving ascites and hepatic encephalopathy and decreasing the amount of variceal bleeds in patients who achieve SVR. Ascites and hepatic encephalopathy are the most common reasons for hospital admission among patients with advanced liver disease, and advanced liver disease is associated with poor quality of life . Furthermore, several studies have demonstrated that HCV patients who achieve SVR with DAAs are likely to experience significant improvements in patient‐reported outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…
B outs of overt hepatic encephalopathy (OHE)-i.e., hepatic encephalopathy (HE) causing at least clear disorientation in time or asterixis (1) -severely hamper autonomy and quality of life, causing a heavy burden on caregivers and health systems. (2) Hyperammonemia plays a crucial role in the pathophysiology of HE, so reducing ammonia levels is currently the primary therapeutic target. However, the link between HE and ammonia is not strict because other factors intervene to alter brain function, principally infection.
…”
mentioning
confidence: 99%